2006
DOI: 10.1191/0748233706th247oa
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Ni and V, other heavy metals, arsenic, elemental and organic carbon in atmospheric fine particles (PM2.5) from Puerto Rico

Abstract: Fine atmospheric particulate PM 2.5 (particles with diameters of <2.5 μm) were sampled in an urban industrialized area -Guaynabo, Puerto Rico ( Figure 1) -and in a reference less polluted site -Fajardo, Puerto Rico -and analyzed for trace metals, and inorganic and organic elemental carbon. PM 2.5 samples were collected from November 2000 to September 2001 using an Andersen Instruments RAAS2.5-400 for periods of 72 h. Metals analyzed were arsenic (As), cadmium (Cd), copper (Cu), iron (Fe), nickel (Ni), lead (Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 46 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…PM 10 and PM 2.5 concentrations Levels of PM 2.5 measured at the area of interest (Table 1) Puerto Rico (Figueroa et al, 2006), but lower than PM 2.5 levels in Italy (Marcazzan et al 2001), China (Ho et al 2002) or Taiwan (Fang et al 1999).…”
Section: Resultsmentioning
confidence: 91%
“…PM 10 and PM 2.5 concentrations Levels of PM 2.5 measured at the area of interest (Table 1) Puerto Rico (Figueroa et al, 2006), but lower than PM 2.5 levels in Italy (Marcazzan et al 2001), China (Ho et al 2002) or Taiwan (Fang et al 1999).…”
Section: Resultsmentioning
confidence: 91%
“…Figueroa et al [12] confirmed that most of the toxic metals in the air occur in the form of fine particles. It is suggested that these metals can produce lung tissue damage by catalyzing oxidant formation [13].…”
Section: F Health Implications Of the Toxic Trace Metalsmentioning
confidence: 94%
“…Also, the U.S. EPA indicated the use of glass or quartz fibre filters for PM collection [44]. In this sense, there are some studies that employ filters made of polycarbonate [50,54,60], PTFE (Teflon) [61][62][63] or glass fibre [46,64,65], although in none of these references a justification is given for the selection of a particular type of material. The properties and blank values for…”
Section: Sampling Of Particulate Mattermentioning
confidence: 99%